Subcellular Localization of Sprouty2 in Human Glioma Cells - Hausott, Barbara; Park, Jong-Whi; Valovka, Taras; Offterdinger, Martin; Hess, Michael W.; Geley, Stephan; Klimaschewski, Lars (Frontiers in Molecular Neuroscience, 2019)
Sprouty proteins act ubiquitously as signaling integrators and inhibitors of receptor tyrosine kinase activated pathways. Among the four Sprouty isoforms, Sprouty2 is a key regulator of growth factor signaling in several neurological disorders. High protein levels correlate with reduced survival of glioma patients. We recently demonstrated that abrogating its function inhibits tumor growth by overstimulation of ERK and induction of DNA replication stress. The important role of Sprouty2 in proliferation of malignant glioma cells prompted us to investigate its subcellular localization applying super-resolution fluorescence and immuno-electronmicroscopy. We found that cytoplasmic Sprouty2 is not homogenously distributed but localized to small spots (< 100 nm) partly attached to vimentin filaments and co-localized with activated ERK. The protein is associated with early, late and recycling endosomes in response to but also independently of growth factor stimulation. The subcellular localization of Sprouty2 in all areas exhibiting strong receptor tyrosine kinase activities may reflect a protective response of glioma cells to limit excessive ERK activation and to prevent cellular senescence and apoptosis.